Sustainable agriculture in the Blue Nile Basin: Land and watershed management practices in Ethiopia - Schmidt, Emily; Tadesse, Fanaye (Cambridge University Press, 2014)
The trade-off between short-term welfare and long-term agricultural development in the highlands of Ethiopia represents a challenge to successful economic development in a predominantly agriculture-based economy. We employ nearest neighbor and kernel-based matching techniques to measure the impact of sustainable land and watershed management (SLWM) on the value of production at the plot level. Analysis suggests that plots that received SLWM investments (terraces, bunds, check dams) within the first study period (1992–2002) had a 24 per cent higher value of production in 2010. In addition, continuous treatment effects analysis provides a robustness check and suggests that plots with existing SLWM infrastructure have a positive and increasing value of production seven years after construction. Although value of production increases over time, net benefits may not outweigh costs, and mechanisms to incentivize maintenance may be needed.